Chemical fertilization of melon (Cucumis melo L.) in greenhouses. A proposal to improve yield and quality - Julio Gabriel Ortega; Rubén Pérez Castillo; Washington Narváez Campana; Jéssica Morán Moran; Alfredo Castro Landín; Gema Burgos López (Journal of the Selva Andina Biosphere)
With the objective of obtaining a chemical fertilization strategy for melon (Cucumis melo L.) fruit production and quality in the greenhouse, 3 doses of chemical fertilization were applied at 3 stages of plant development. The treatments were distributed in a completely randomized block experimental design with 4 replications. Each experimental unit had 3 rows. Each row had 41 plants and the experimental unit for each treatment was 123 plants. The results indicate that the best fertilization level was for T2, obtaining an average weight per fruit of 0.97 kg, compared to the control, which was 0.58 kg. It was also observed that T2 was the best for pulp refractive index, core refractive index and core total solids, which resulted in better quality fruit. In the Pearson correlation analysis, with positive and highly significant correlations for all the variables compared (r > 0.70). Finally, the benefit/cost analysis, for supermarkets and the grocery market, determined that T2 was the most profitable with a B/C ratio of $3.10 in the supermarket and $1.46 in the grocery market, indicating that for each dollar invested, $2.10 and 46 cents are earned, respectively.